Mural Cell SRF Controls Pericyte Migration, Vessel Patterning and Blood Flow. Issue 4 (14th July 2022) - Orlich, Michael M.; Diéguez-Hurtado, Rodrigo; Muehlfriedel, Regine; Sothilingam, Vithiyanjali; Wolburg, Hartwig; Oender, Cansu Ebru; Woelffing, Pascal; Betsholtz, Christer; Gaengel, Konstantin; Seeliger, Mathias; Adams, Ralf H.; Nordheim, Alfred
Abstract : Background: Pericytes and vascular smooth muscle cells, collectively known as mural cells, are recruited through PDGFB (platelet-derived growth factor B)-PDGFRB (platelet-derived growth factor receptor beta) signaling. MCs are essential for vascular integrity, and their loss has been associated with numerous diseases. Most of this knowledge is based on studies in which MCs are insufficiently recruited or fully absent upon inducible ablation. In contrast, little is known about the physiological consequences that result from impairment of specific MC functions. Here, we characterize the role of the transcription factor SRF (serum response factor) in MCs and study its function in developmental and pathological contexts. Methods: We generated a mouse model of MC-specific inducible Srf gene deletion and studied its consequences during retinal angiogenesis using RNA-sequencing, immunohistology, in vivo live imaging, and in vitro techniques. Results: By postnatal day 6, pericytes lacking SRF were morphologically abnormal and failed to properly comigrate with angiogenic sprouts. As a consequence, pericyte-deficient vessels at the retinal sprouting front became dilated and leaky. By postnatal day 12, also the vascular smooth muscle cells had lost SRF, which coincided with the formation of pathological arteriovenous shunts. Mechanistically, we show that PDGFB-dependent SRF activation is mediated via MRTF (myocardin-related transcription factor) cofactors. We further show that MRTF-SRF signaling promotes pathological pericyte activation during ischemic retinopathy. RNA-sequencing, immunohistology, in vivo live imaging, and in vitro experiments demonstrated that SRF regulates expression of contractile SMC proteins essential to maintain the vascular tone. Conclusions: SRF is crucial for distinct functions in pericytes and vascular smooth muscle cells. SRF directs pericyte migration downstream of PDGFRB signaling and mediates pathological pericyte activation during ischemic retinopathy. In vascular smooth muscle cells, SRF is essential for expression of the contractile machinery, and its deletion triggers formation of arteriovenous shunts. These essential roles in physiological and pathological contexts provide a rationale for novel therapeutic approaches through targeting SRF activity in MCs.